2018
DOI: 10.1111/jre.12543
|View full text |Cite
|
Sign up to set email alerts
|

Increased systemic levels of inflammatory mediators following one‐stage full‐mouth scaling and root planing

Abstract: FM-SRP resulted in clinical and microbiological improvement 6 weeks post-treatment, but produced a moderate systemic acute-phase response including elevated inflammatory mediators 1 day post-treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 67 publications
7
68
0
1
Order By: Relevance
“…The values of significance that we obtained are only demonstrated by Shaddox et al, with higher percentages of IFNγ ( p < 0.001) [ 6 ] in the sites taken into consideration compared to healthy sites. Still, similar values were obtained by Thunell ( p < 0.0001) [ 7 ] and Marazumi ( p < 0.001) [ 8 ]. Finally, Zhang et al found a correlation between the transcriptional levels of IFNγ and the periodontitis with values of p = 0.04 [ 9 ].…”
Section: Resultssupporting
confidence: 85%
“…The values of significance that we obtained are only demonstrated by Shaddox et al, with higher percentages of IFNγ ( p < 0.001) [ 6 ] in the sites taken into consideration compared to healthy sites. Still, similar values were obtained by Thunell ( p < 0.0001) [ 7 ] and Marazumi ( p < 0.001) [ 8 ]. Finally, Zhang et al found a correlation between the transcriptional levels of IFNγ and the periodontitis with values of p = 0.04 [ 9 ].…”
Section: Resultssupporting
confidence: 85%
“…Furthermore, it should be keep in mind that oral therapeutic procedures could, per se, trigger an inflammatory host response 30 . Recently, Morozumi et al 31 reported a moderate systemic acute-phase response in addition to clinical and microbiological improvements after full-mouth procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the clinical parameters improved dramatically post‐FM‐SRP. For example, we previously reported that gingival crevicular fluid IL‐6 and serum hs‐CRP levels increased markedly one day postprocedure, and elevated body temperature was observed in many patients postoperatively …”
Section: Discussionmentioning
confidence: 99%
“…Our analysis showed that FM-SRP resulted in clinical and microbiological improvements 6 weeks posttreatment but produced a moderate systemic acute-phase response, including elevated inflammatory mediators, one day posttreatment. 12 However, the use of FM-SRP while using antibiotics has been reported to improve clinical parameters and the amount of periodontal pathogenic bacteria, in addition to inhibiting the elevation of body temperature. 13 This result seems to indicate that antibiotics can suppress the inflammatory reaction induced by FM-SRP.…”
Section: Introductionmentioning
confidence: 99%